Law as religion, religion as law - Flatto, David C.; Porat, Benny (Cambridge University Press, 2022)
"The problem of absolutes" refers to the difficulty of grounding and defending absolute prohibitions in a legal system that is rationalized on the basis of means-ends rationality. (An example might be the difficulty in identifying an absolute prohibition on torture that is not susceptible to being reinterpreted, read down, or negotiated away.) In the present paper, I associate this difficulty in the first instance with Max Weber's account of the rationalization of law and the distancing of law from any sense of sacred or transcendent obligation. But other developments need to be considered as well. I argue that the problem is as much about morality as it is about law. The two-law and morality-develop together in a complementary way, and the problem of legal absolutes tends to be matched by a corresponding difficulty with moral absolutes, just as the desanctification of law tends to be matched by a desanctification of morality"--